Information technology in dental clinical examination of high school students - E. A. Bidnyuk; L. S. Godlevskiy; N. R. Bayazitov (Zaporožskij Medicinskij Žurnal)
The peculiarities of dentistry dispanserization of school - children have been investigated with the usage of IDEF modeling of the process of this process. The role played by all participants, who have been involved into process of dispanserization have been done. Besides, the results of repeated advertisements of children have been done with the emphasis on the role of medical recommendation(s) inscription into electronic forms of documents, which are used by them at school and which have been designed for listing their academic records. Namely, electronic diary forms have been used with that purpose. It was established that recommendations which have been located in electronic diary improved the medical results as far as children have been followed them on more responsible basis.